2016
DOI: 10.1111/myc.12535
|View full text |Cite
|
Sign up to set email alerts
|

Differences in epidemiology of candidaemia in the Nordic countries – what is to blame?

Abstract: National data from Denmark, Finland, Norway and Sweden demonstrate remarkable differences in candidaemia epidemiology. Only Denmark has reported a high incidence of 10 per 100 000 inhabitants and a species shift towards increased C. glabrata candidaemias. The reasons for this development remain unclear. The aim of this study was to explore possible contributing factors for the differences in Candida epidemiology in the Nordic countries. We used public data from 2011 from Denmark, Finland, Norway and Sweden on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
3
30
2
1
Order By: Relevance
“…Several studies have reported a redistribution of species, with a decrease in the number of C. albicans . This was also the case in this study (54.7% in 2015‐2016 vs 61% in 2005‐2006) but we did not see any increase of C. glabrata , as reported from Denmark and Australia and no increase of C. parapsilosis. C. glabrata was still predominant in patients >60 years of age (83%) in 2015‐2016 with similar rates in 2005‐2006.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Several studies have reported a redistribution of species, with a decrease in the number of C. albicans . This was also the case in this study (54.7% in 2015‐2016 vs 61% in 2005‐2006) but we did not see any increase of C. glabrata , as reported from Denmark and Australia and no increase of C. parapsilosis. C. glabrata was still predominant in patients >60 years of age (83%) in 2015‐2016 with similar rates in 2005‐2006.…”
Section: Discussionsupporting
confidence: 83%
“…Studies from the USA report higher Candida incidence rates compared to those from the European countries . Denmark is an exception where the rate is close to that of the USA with an incidence of 10 per 100 000 inhabitants and a species shift towards increased C. glabrata candidaemias. The use of antifungal drugs as well as antibacterial drugs has been proposed to shift the Candida species distribution …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Denmark is known for a consistently high annual incidence rate of candidaemia of 7.6-11.0 episodes per 100,000 inhabitants since nationwide surveillance was introduced in 2004. In comparison, annual rates of 3.9-4.4 episodes per 100,000 inhabitants have been reported in similar studies from neighbouring Scandinavian countries (Arendrup et al, 2013;Hesstvedt et al, 2017;Arendrup et al, 2008). Nationwide annual data from other countries are sparse and limited to Australia with 2.4 per 100,000 inhabitants (Chapman et al, 2017), and Scotland with 4.1 per 100,000 inhabitants (Rajendran et al, 2016).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 86%
“…In Scotland, MRSA generally does not show greater virulence than MSSA; however, the efficacy of antimicrobial therapy is reduced. In addition, carbapenem therapy leads to Candidal overgrowth and promotion of resistant coliforms . Risk of CDI is reportedly increased in people over 65 years, immunosuppressed, hospital inpatients, those on proton pump inhibitor agents and those who have previously experienced CDI .…”
Section: Antibiotic Therapy: Risks Benefits and Complicationsmentioning
confidence: 99%